'You're Just Thinking About Going Home': Exploring Person‐Centred Medication Communication With Older Patients at Hospital Discharge - Henrik Cam; Kristin Franzon; Sofia Kälvemark Sporrong; Thomas Gerardus Hendrik Kempen; Cecilia Bernsten; Elisabet I. Nielsen; Lovisa Gustavsson; Elnaz Moosavi; Stina Lindmark; Ulf Ehlin; Maria Sjölander; Karl‐Johan Lindner; et al. (Wiley, 2024)
ABSTRACT Background The hospital discharge process poses significant safety risks for older patients due to complexities in communication and coordination among stakeholders, leading to potential drug‐related problems post‐discharge. Adopting a person‐centred care (PCC) approach in medication communication by healthcare professionals (HCPs) is crucial to ensure positive health outcomes. This study aimed to explore the practice of PCC in medication communication between older patients and HCPs during the hospital discharge process. Methods We conducted a qualitative study using non‐participatory direct observations of patient-HCP consultations during hospital discharge, followed by semi‐structured interviews with observed patients and, when applicable, their informal caregivers. Data collection occurred from October 2020 to May 2021 at two Swedish hospitals. We gathered data using an observational form and audio‐recorded all consultations and interviews. The data were analysed thematically using the systematic text condensation method. Results Twenty patients were included (median age: 81 years [range: 65-94]; 9 female) in observations and 13 of them participated in interviews. Two patients were accompanied by an informal caregiver during the interviews. Three main themes were identified: (1) The impact of traditional authoritarian structures, depicts power dynamics between patients and their HCPs, showing how traditional structures influence the practice of PCC in medication communication during hospital discharge; (2) Consultation timing and mode not on patients' terms, describes suboptimal times and settings for consultations, along with the use of complex language that hinders effective communication; and (3) Discrepancy in expectations of self‐care ability, illustrates a mismatch between the self‐care guidance provided by HCPs during hospital discharge and the actual needs and preferences of patients and informal caregivers. Conclusion Medication communication between older patients and HCPs during hospital discharge is frequently inconsistent with the practice of PCC. Not only must HCPs improve their communication strategies, but patients and their informal caregivers should also be better prepared for discharge communication and encouraged to participate in their care. This involvement would give them relevant knowledge and tailor communication to their individual needs, preventing problems in managing their medications after discharge. Patient or Public Contribution An advisory group of six patients and/or informal caregiver contributors provided input on the study design, edited the consent forms, and helped develop the interview guide.